2020
DOI: 10.1021/acs.nanolett.0c02285
|View full text |Cite
|
Sign up to set email alerts
|

Polar Nanodomains in a Ferroelectric Superconductor

Abstract: The mechanisms by which itinerant carriers compete with polar crystal distortions are a key unresolved issue for polar superconductors, which offer new routes to unconventional Cooper pairing. Strained, doped SrTiO 3 films undergo successive ferroelectric and superconducting transitions, making them ideal candidates to elucidate the nature of this competition. Here, we reveal these interactions using scanning transmission electron microscopy studies of the evolution of polar nanodomains as a function of doping… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

2
28
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 43 publications
(30 citation statements)
references
References 46 publications
(84 reference statements)
2
28
0
Order By: Relevance
“…For example, it has been reported that in-plane compressive strain can enhance the T C of SrTiO 3 by up to a factor of two, resulting from the strain-induced modification of phonon modes [39]. More study further revealed that both strain and disorder could control T C [40,41]. A systematic increase of T C with epitaxial tensile strain in MgB 2 films has also been reported, resulted from the softening of the bondstretching phonon mode [42].…”
Section: Resultsmentioning
confidence: 96%
“…For example, it has been reported that in-plane compressive strain can enhance the T C of SrTiO 3 by up to a factor of two, resulting from the strain-induced modification of phonon modes [39]. More study further revealed that both strain and disorder could control T C [40,41]. A systematic increase of T C with epitaxial tensile strain in MgB 2 films has also been reported, resulted from the softening of the bondstretching phonon mode [42].…”
Section: Resultsmentioning
confidence: 96%
“…This sensitivity, combined with the low temperatures, makes detailed characterization of the structure of the quantum paraelectric state challenging: Neutron and x-ray Rietveld analysis of STO, for example, indicate a centrosymmetric structure down to 1.5 K [15]. In contrast, nuclear magnetic resonance (NMR) shows local dynamic polar off-centering of the Ti ions [16], consistent with the anomalous vibrational amplitudes seen in γ-ray Bragg scattering [17], and scanning transmission electron microscopy reveals local polar nanoregions [18].…”
Section: Introductionmentioning
confidence: 92%
“…Moreover, SrTiO 3 can also be a polar superconductor that undergoes a ferroelectric transition prior to becoming superconducting. [3][4][5] In superconductors with broken inversion symmetry spin-orbit coupling becomes important, which can lead to unconventional superconductivity. [6][7][8][9] A test of the nature of a superconductor is its response to disorder.…”
mentioning
confidence: 99%
“…Surprisingly, however, the superconducting transition temperatures (T c ) and the superconducting dome are identical for magnetic and non-magnetic dopants. 3,23,24 While there are indications that disorder from the dopant atoms is detrimental to superconductivity in SrTiO 3 , 5 the insensitivity to their magnetic moment does not easily fit within a conventional picture of isolated magnetic impurities that would strongly suppress the transition temperature of the superconductor.…”
mentioning
confidence: 99%
See 1 more Smart Citation